Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 5 - Exponents and Polynomials - Chapters 1-5 Cumulative Review Problem Set - Page 233: 9



Work Step by Step

First, we will simplify the expression within the parenthesis by finding the least common denominator: $(\frac{1}{2}-\frac{1}{3})^{-2}$ =$(\frac{1(3)-1(2)}{6})^{-2}$ =$(\frac{3-2}{6})^{-2}$ =$(\frac{1}{6})^{-2}$ Next, we raise both the numerator and the denominator to the power of $-2$ and simplify: $(\frac{1}{6})^{-2}=\frac{1^{-2}}{6^{-2}}=\frac{6^{2}}{1^{2}}=36$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.